FRAUD PENTAGON IN DETECTING FINANCIAL STATEMENT FRAUD - Fityan Izza Noor Abidin; Riza Arista Firana; Sarwenda Biduri (Antis Publisher, 2025)
Objective: This study aims to analyze the influence of the fraud pentagon elements on financial statement fraud in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2016–2020 period. Method: A quantitative approach was employed using secondary data derived from company annual reports. The sample consisted of 12 companies selected through purposive sampling, resulting in 60 firm-year observations. Results: The findings reveal that the elements of pressure, opportunity, rationalization, competence, and dualism position significantly affect the likelihood of financial statement fraud. In contrast, the frequency of CEO photographs in annual reports was found to have no significant impact. Novelty: This study highlights the critical role of dualism in leadership positions as a contributing factor to fraudulent reporting, offering new insights into corporate governance concerns specific to the Indonesian context. These results underscore the necessity for strengthened monitoring mechanisms and enhanced governance to reduce the risk of fraudulent financial reporting and support the integrity of financial disclosures.